Konsep Dakwah Islam Rahmatan Lil’alamin Dalam Majalah Bangkit - Arina Rahmatika; Ninda Khoirullina (Jurnal Dakwah dan Komunikasi, 2021)
The purpose of this research is to discuss how the discourse of the concept of Islamic da'wah by Rahmatan Lil'alamin according to Bangkit Magazine is seen from its main ideas to the characteristics of its preaching. Islam is a religion that was revealed by Allah SWT to the Prophet Muhammad SAW which regulates the relationship between humans and God and also regulates the relationship between humans and humans and the universe which benefits each other, therefore Islam has the principle of Rahmatan lil 'Alamin, which is a blessing for the universe. This research in extracting data using direct interviews to magazine administrators, literature study and documentation. From the research results, it can be found that Islam Rahmatan lil 'Alamin according to Bangkit Magazine is an Islam that is peaceful, just, tolerant and in accordance with the values of aswaja. The definition of Rahmatan lil 'Alamin is also not much different from the big concept of Islam which is in accordance with the teachings of NU (Nahdlatul Ulama). Islamic Perspective Rahmatan lil 'Alamin Bangkit Magazine is also sustainable with the characteristics of Islam Rahmatan lil' Alamin including non-violence, prioritizing peace, brotherhood, mutual respect and good things. As for the solution to restore the current image of Islam, namely by making Islam Rahmatan lil 'Alamin as a protector in preaching, with that Islam will also gradually create a vision full of tenderness and peace.